Religious Moderation in Indonesian Classrooms: Reflective and Participatory Pedagogy in a Multifaith School Context - Sihotang, Din Oloan; Waruwu, Ermina; Lumbanbatu, Johannes Sohirimon; Setiyaningtiyas, Nerita; Odongo, John Bosco (UIN Sunan Gunung Djati Bandung, 2024)
This study examines the effectiveness of integrating the Iceberg Analysis and the U-Process as a pedagogical framework to promote religious moderation in a multifaith Indonesian secondary school. Given the rising concern over religious intolerance and youth vulnerability to radical ideologies in pluralistic societies, the study addresses the urgent need for reflective and participatory learning approaches that can transform attitudes and behaviours. Employing a mixed-methods design, the research involved 100 students of different religious and ethnic backgrounds at SMA Negeri 1 Barus Jahe, North Sumatra. Data were collected through pre-tests, post-tests, questionnaires, classroom observations, and student reflections. Thematic and statistical analyses revealed significant improvements in students’ understanding, awareness, and enactment of religious moderation values, with average cognitive scores increasing from 55 to 81.5 and behavioural awareness from 48.75 to 78.25. These findings suggest that integrating the Iceberg Analysis and U-Process facilitates cognitive development and deep emotional and ethical internalisation of interfaith values. The study contributes to religious education by proposing a culturally contextualised and empirically validated model that bridges conceptual understanding and real-world practice. Its originality lies in synthesising two transformative learning approaches into a unified pedagogical strategy tailored for pluralistic and multicultural settings, with practical implications for curriculum design, teacher training, and interfaith peacebuilding.